A experiência como marca e fonte do saber na fé Pentecostal: um breve estudo histórico-teológico = Alternativtitel: Experience as a mark and source of knowledge in pentecostal faith : a brief historical-theological study - Lima, Daniel Barros de (Plura, revista de estudos de religião, 2025)
This article investigates experience as an identity marker and source of knowledge in Pentecostal faith, through a historical-theological analysis of Pentecostalism and accounts of glossolalia, healing, and ecstasy as practical validation of doctrine. Drawing on a thematic fragment of a 2020 dissertation, it argues that Pentecostal spirituality articulates implicit values—individual experience, verbalism, spontaneity, supernaturalism, and biblicism. These values structure a devotional habitus in which the experience of the Spirit functions as a lived hermeneutic of the biblical text. In dialogue with Jürgen Moltmann, Clodovis Boff, Edward Thompson, Kenner Terra, David Mesquiati, and Gedeon Alencar, the study shows how published testimonies (e.g., healing narratives by believers) operate as practical theology and a "catechism of experience," converting lived events into a criterion of truth and into symbolic capital for communal cohesion within Pentecostal communities. It concludes that, since the beginnings of Pentecostal faith, experience is not a mere devotional addendum but an epistemic device that organizes belief, ethics, and belonging, offering methodological keys for investigating religious ecstasy from a historical-theological perspective.